Mechanisms, efficiency and safety of pharmacopuncture - L. G. Agasarov; O. S. Davyan (Лечащий Врач, 2021)
The article is devoted to the therapeutic characteristics of pharmacopuncture (otherwise, biopuncture) — a method based on the administration of medications in the area of reflexotherapy points. The presented material is the result of many years of own research, built on the use of a «model» of vertebrogenic pathology.